Bacterial Colonization and Vertical Distribution of Marine Gel Particles (TEP and CSP) in the Arctic Fram Strait - Busch, Kathrin; Endres, Sonja; Iversen, Morten H.; Michels, Jan; Nöthig, Eva-Maria; Engel, Anja (Frontiers in Marine Science, 2017)
Gel particles - a class of abundant transparent organic particles - have increasingly gathered attention in marine research. Field studies on the bacterial colonization of marine gels however are still scarce. So far most studies on respective particles have focused on the upper ocean while little is known on their occurrence in the deep sea. Here, we report on the vertical distribution of the two most common gel particle types, which are polysaccharide-containing transparent exopolymer particles (TEP) and proteinaceous Coomassie stainable particles (CSP), as well as numbers of bacteria attached to gel particles throughout the water column, from the surface ocean down to the bathypelagial (< 3000 m). Our study was conducted in the Arctic Fram Strait during northern hemispheres' summer in 2015. Besides data on the bacterial colonization of the two gel particle types (TEP and CSP), we present bacterial densities on different gel particle size classes according to twelve different sampling depths at four sampling locations. Gel particles were frequently abundant at all sampled depths, their concentrations decreased from the euphotic zone to the dark ocean. They were colonized by bacteria at all sampled water depths; with risen importance at the deepest water layers, where fractions of bacteria attached to gel particles [%] increased within the total bacterial community. Due to the omnipresent bacterial colonization of gel particles at all sampled depths in our study, we presume that euphotic production of this small organic matter may affect microbial species distribution within the whole water column in the Fram Strait, down to the deep sea. Our results raise the question if changes in the bacterial community composition and functioning on gel particles occur over depth, which may affect microbial respiration and remineralization rates of respective particles in different water layers.